Recent advances in basic neurosciences and brain disease: from synapses to behavior - Salter Michael W; Roder John C; Ren Ke; Oh Uhtaek; Nguyen Peter V; Nader Karim; MacDonald John F; Li Xiao-Jiang; Li Min; Kohno Tatsuro; Klann Eric; Kida Satoshi; et al. (SAGE Publishing, 2006)
Abstract Understanding basic neuronal mechanisms hold the hope for future treatment of brain disease. The 1st international conference on synapse, memory, drug addiction and pain was held in beautiful downtown Toronto, Canada on August 21-23, 2006. Unlike other traditional conferences, this new meeting focused on three major aims: (1) to promote new and cutting edge research in neuroscience; (2) to encourage international information exchange and scientific collaborations; and (3) to provide a platform for active scientists to discuss new findings. Up to 64 investigators presented their recent discoveries, from basic synaptic mechanisms to genes related to human brain disease. This meeting was in part sponsored by Molecular Pain, together with University of Toronto (Faculty of Medicine, Department of Physiology as well as Center for the Study of Pain). Our goal for this meeting is to promote future active scientific collaborations and improve human health through fundamental basic neuroscience researches. The second international meeting on Neurons and Brain Disease will be held in Toronto (August 29-31, 2007).